Predictor role of marital conflict on maternal competency with mediating role of perceived stress and concerns during pregnancy: A structural equation model - Sepideh Mohammad Alipour; Mitra Rahimzadeh; Zahra Mehdizadeh Tourzani; Zohreh Mahmoodi; Sara Esmaelzadeh Saeieh (Wiley, 2023)
Abstract Aim Pregnancy prepares the mother for the transition to motherhood. Maternal concerns during pregnancy cause reduced time spent with the spouse and lack of social support; additional stresses such as marital conflicts could impact maternal competency. This study aimed to assess the predictive effect of marital conflicts with the mediating role of perceived stress and pregnancy concern on maternal competency. Methods This was a longitudinal study. It was done on 250 mothers referred to selected health centers in Alborz province. The sampling method was convenient. Marital conflicts, perceived stress, and pregnancy concerns questionnaires were completed in the third trimester of pregnancy, and the maternal competency questionnaire was completed 6 weeks after delivery. Data were analyzed by SPSS software and smart partial least squares. Results The results of structural equations showed that marital conflicts have a negative and significant effect on maternal competency (β = −0.14), marital conflicts have a positive and significant effect on perceived stress (β = 0.42), and marital conflicts have a positive and significant effect on pregnancy concern (β = 0.31). Also, perceived stress negatively and significantly affected maternal competency (β = −0.36). Discussion Results of the study showed the necessities for screening and identifying mothers with conflicts and assessing the perceived stress of mothers will improve the mental health of pregnant mothers and consequently increase maternal competency.